The Power or Impotence of the Image? Toward the Semiotic Analysis of Edith Stein’s Representations in Cyberspace - Machtyl, Katarzyna (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
The author poses several questions: is it possible for the saint to have a digital image? Can we analyse the presence of the saint in cyberspace and is a semiotic view in this field possible? The main aim of the article is to indicate some of visual semiotic concepts, including those referring to digital images, and applying them to selected representations of Edith Stein found on the Internet. Firstly, the author tries to recognise differences between concepts and notions connected to visuality (for example picture, image and representation). In the next part, there is a passage dedicated to the concepts of presence and non-presence, action and signification of an image on the Internet. In the main part of the text the author describes and analyses selected images of Edith Stein found in cyberspace using a semiotic approach. The last passage contains a presentation of two different iconoclasm’s concepts: the theological and the poststructural.